Research on shearer positioning with double-INS. Issue 4 (15th July 2019) - Wang, Shijia
Abstract : Purpose: This paper aims to improve shearer positioning accuracy. Shearer positioning using an inertial navigation system (INS) is a highly useful technology; however, positioning accuracy is seriously hindered by INS attitude error, particularly heading drift. Design/methodology/approach: A shearer positioning model with double-INS based on extended Kalman filter was proposed. The constant distance between two INSs (INS 1 and INS 2) was selected as the observation vector. Allan variance was used to identify the noise type of the vertical-axis gyroscope, and the stochastic process of heading drift for two INSs was obtained and divided into incongruous drift and concurrent drift. Findings: Simulation was then carried out to determine the optimal arrangement of the two INSs. For incongruous drift, the optimal arrangement satisfied the condition that the line connecting INS 1 and INS 2 was perpendicular to the shearer lateral axis (in the shearer coordinate frame) and parallel to the east-north plane (in the east-north-up coordinate frame). Under optimal arrangement, the positioning accuracy increased against the distance between INS 1 and INS 2. For concurrent drift, the double-INS positioning model had no effect. Under the circumstances, the number of INSs should be increased so that the uncertainty of INS drift was reflected as much as possible. Originality/value: A new double-INS positioning model was proposed with the constant distance between the two INSs. The optimal arrangement for double-INS was obtained.